Dry-method electrode aggregate manufacturing method, dry-method electrode pole piece manufacturing method and secondary battery
By using the differential double stirring spiral structure of the homogenizer in the dry electrode preparation process for homogenization, the problem of uneven distribution of the electrode dry powder particle size is solved, the uniformity and toughness of the electrode film are improved, and the electrode is ensured. Consistency and stability of performance.
Patent Information
- Application Number
- CN202411408844.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-17
AI Technical Summary
In the existing dry electrode preparation process, the particle size distribution of the fibrotic electrode dry powder after fibrosis is uneven, resulting in uneven distribution of fibrotic PTFE of the electrode film, affecting the consistency and stability of the toughness of the membrane and the electrode performance.
The homogenizer is used to homogenize the differential double stirring spiral structure. Through initial refining and continuous refining, combined with the addition of solvent, kneading and dispersing of powder, homogeneous pellets with uniform particle size are prepared to ensure PTFE fibers and Even distribution of light and heavy materials.
It significantly improves the uniformity and toughness of the film body, ensures the consistency and stability of the electrode performance, and provides a more reliable guarantee for the electrode electrochemical performance.
Smart Images

Figure CN119318913A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dry electrode preparation, in particular to a dry electrode granule preparation method, a dry electrode pole piece preparation method and a secondary battery. Background Art
[0002] With the increasing demand for new energy vehicles and energy storage, increasing battery energy density, reducing costs, and improving cycle performance have become the key to the green development of the lithium battery industry. The traditional wet electrode manufacturing process has limitations in terms of electrode thickness, energy density, and manufacturing cost. As an emerging solution, dry electrode technology is gradually gaining attention in the industry.
[0003] At present, the conventional dry electrode preparation process mostly uses high-speed mixing and airflow grinding technology to fiberize the polytetrafluoroethylene (PTFE) in the electrode after mixing. Figure 1 The figure shows the electrode dry powder after fiberization. During the fiberization process, the molecular chains of the powder will stick together to form agglomerates. Figure 1 It can also be seen that the electrode dry powder after fiberization contains many large lumps, and the distribution of light and heavy materials is uneven. In the prior art, the electrode dry powder after fiberization is usually processed in the following ways: the first way is to directly put the electrode dry powder after fiberization into a calender and roll it into an electrode film. The second way is to crush the electrode dry powder after fiberization, then put it into a calender and roll it into an electrode film; Figure 2 The figure shows the electrode dry powder after crushing and granulation. After the electrode dry powder is crushed and granulated, the powder agglomerates are broken into fine powder. Figure 2 It can be seen that the powder particles after crushing are not clear, the particle sizes are different, the powder contains small lumps with larger particle sizes, and also contains fine powder with very small particle sizes. The particle size distribution is still not uniform. It can be seen that whether it is the electrode dry powder after fiberization or the electrode dry powder after crushing, there is an uneven particle size distribution and uneven distribution of fiberized PTFE. Therefore, if Figure 3 As shown, after the electrode dry powder is calendered into an electrode membrane, there will be an uneven distribution of fibrous PTFE on the electrode membrane, or there will be an uneven distribution of light and heavy materials during calendering. These undesirable conditions will cause different toughnesses in different areas of the membrane after dry film forming, reducing the physical properties of the membrane, and further affecting the consistency and stability of the electrode performance of the subsequent formed electrode. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned existing dry electrode preparation process, the applicant provides a reasonable dry electrode granule production method, a dry electrode pole piece production method, and a secondary battery, and homogenizes the electrode powder after fiberization to improve the particle size uniformity of the powder and the balance of fiberized PTFE distribution.
[0005] The technical solution adopted by the present invention is as follows: A method for preparing dry electrode granules comprises the following steps: The active material, the conductive agent, the trace additive and the binder are mixed to obtain a mixed material; Performing fiberization treatment on the mixed material to obtain a fiberized material; The fiberized material is homogenized by a homogenizer. After initial internal kneading and continued internal kneading in the homogenizer, the fiberized material is prepared into millimeter-scale homogenous granular material.
[0006] As a further improvement of the above technical solution: The homogenizer is provided with a differential double stirring spiral structure, which can adopt a differential double stirring Σ-type blade structure, or a differential double screw structure, or a vertical differential double-axis stirring paddle structure. The blades of the No. 1 stirring spiral structure have opposite spiral directions to the blades of the No. 2 stirring spiral structure.
[0007] The rotation speed of the No. 1 stirring spiral structure of the homogenizer is 40 to 80 r / min, and the rotation speed of the No. 2 stirring spiral structure is 10 to 70 r / min.
[0008] After the initial kneading of the fiberized material, a solvent is added and the kneading is continued. The added solvent is viscous.
[0009] The mass percentage of the added solvent is 0-20%; the solvent is viscous, and the viscosity range is 1-5000cP; the solvent is a mixture of polytetrafluoroethylene suspension and polyvinylidene fluoride suspension, or polyvinylidene fluoride suspension, or sodium carboxymethyl cellulose suspension, or alcohol.
[0010] During homogenization, the initial mixing temperature range is 15 to 90° C., the mixing time of the initial mixing is 10 to 40 minutes, and the mixing time of the continued mixing is 20 to 60 minutes; the particle size of the homogenized granules is 1 to 5 mm.
[0011] When mixing materials, active substances, conductive agents, trace additives and binders are uniformly mixed in batches, two or more of the materials are first mixed and dispersed or coated, and then the remaining materials are added for mixing and dispersion; the trace additives are one or more of graphite, carbon nanotubes, carbonates, phosphates, and silicate minerals; the binder is one or more of polytetrafluoroethylene suspension, polyvinylidene fluoride suspension, polyvinylidene fluoride suspension, styrene-butadiene rubber emulsion, sodium carboxymethyl cellulose suspension, and alcohols.
[0012] The mixed material is fiberized by an air jet mill. The pressure of the compressed air introduced into the air jet mill is 0.5-1MPa, the temperature is 50-100°C, and the humidity is 1%-5%. The air jet mill type is one of the disc air jet mill, circulating tube air jet mill, target air jet mill, jet air jet mill or fluidized bed air jet mill.
[0013] A dry electrode plate manufacturing method is disclosed, wherein the homogeneous granular material manufactured according to the dry electrode granular material manufacturing method is subjected to calendering and thinning treatment to obtain a finished film, and the finished film is compounded with a current collector to obtain an electrode plate.
[0014] A secondary battery is made using the electrode sheet made according to the dry electrode sheet making method.
[0015] The beneficial effects of the present invention are as follows: The present invention introduces a homogenous agglomeration granulation technology, and further realizes the uniform dispersion of the fiberized material after blowing, mixing and drawing through the shearing force of the differential double stirring spiral structure, and at the same time utilizes the characteristics of the PTFE fibrous structure to efficiently integrate the powder material. The homogenous agglomeration granulation process includes the actions of kneading and breaking up: under the shearing force of the differential double stirring spiral structure, the powders of different particle sizes are first kneaded into larger agglomerates, and then the agglomerates are evenly broken up to reach a balanced state after the particle size requirements are met; the granules prepared in this way have basically the same particle size, and the particle size distribution is more uniform, which ensures the uniform distribution of PTFE fibers and light and heavy materials in the film forming process, and significantly improves the uniformity and toughness of the film. Through this optimized dry electrode preparation process, not only the physical properties of the film are improved, but also the consistency and stability of the electrode performance are ensured, providing a more reliable technical guarantee for the electrochemical performance of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the state diagram of the electrode powder after fiberization.
[0017] Figure 2 This is the state diagram of the electrode powder after crushing and granulation.
[0018] Figure 3 This is a state diagram of the electrode film pressed from the crushed and granulated electrode powder.
[0019] Figure 4 The figure is a flow chart of the pole piece production of the present invention.
[0020] Figure 5 This is the state diagram of the electrode powder after homogenization.
[0021] Figure 6 This is a state diagram of the electrode film rolled out from the electrode powder after homogenization.
[0022] Figure 7 This is a state diagram of the electrode pellets produced in Example 1 of electrode pellet production.
[0023] Figure 8 This is a state diagram of the electrode pellets produced in Example 3 of electrode pellet production.
[0024] Fig. 9 It is a schematic structural diagram of the first embodiment of the differential speed double stirring spiral structure of the homogenizer.
[0025] Fig.10 It is a schematic structural diagram of the second embodiment of the differential speed double stirring spiral structure of the homogenizer.
[0026] Fig.11 It is a schematic structural diagram of the third embodiment of the differential speed double stirring spiral structure of the homogenizer.
[0027] In the figure: 100, homogenizer; 10, stirring spiral structure No. 1; 20, stirring spiral structure No. 2; 1, stirring shaft; 2, paddle; 21, notch. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is described below in conjunction with the accompanying drawings.
[0029] like Figure 4 As shown, the dry electrode plate manufacturing method described in the present invention includes a dry electrode granule manufacturing method. After the electrode granules are made of dry electrode granules, they are rolled and thinned to obtain a dry film. The dry film and the collector are sent to a composite device for composite to obtain an electrode plate. The electrode plate can be used to make a secondary battery.
[0030] The dry electrode production method mainly includes the following steps: S1, mixing materials to obtain a mixed material; S2, fiberization treatment to obtain fiberized material; S3, homogenization treatment to obtain homogeneous granules; S4, calendering to obtain an initial film; S5, thinning to obtain a finished film; S6. Compounding with the current collector to obtain an electrode plate.
[0031] The following is a detailed description of each step: Step S1: In this step, the active material, the conductive agent, the trace additive and the binder are uniformly mixed in batches to obtain a mixed material. The trace additive is one or more of graphite, carbon nanotubes, carbonates, phosphates, and silicate minerals, and the amount of the trace additive is less than 3%. The binder is one or more of polytetrafluoroethylene suspension, polyvinylidene fluoride suspension, polyvinylidene fluoride suspension, styrene-butadiene rubber emulsion, sodium carboxymethyl cellulose suspension, and alcohols. Uniform mixing in batches refers to mixing and dispersing two or more materials or coating them first, and then adding the remaining materials for mixing and dispersing, so that a variety of materials with certain viscosity and easy to agglomerate can be prevented from being added at the same time, which is more conducive to the uniform dispersion of materials.
[0032] Step S2: In this step, the mixed material is added to the air flow mill, and compressed air satisfying the pressure, temperature and humidity is introduced into the air flow mill to perform fiberization on the mixed material to obtain a fiberized material. The air flow mill type can be a disc air flow mill, a circulating tube air flow mill, a target air flow mill, a jet air flow mill or a fluidized bed air flow mill. The pressure of the compressed air introduced is 0.5-1MPa, the temperature is 50-100°C, and the humidity is 1%-5%. The state of the fiberized material is as follows: Figure 1 shown.
[0033] Step S3: In this step, the fiberized material is fed into the homogenizer 100 for homogenization to obtain homogenized granules. After the fiberized material is fed into the homogenizer 100, it is first subjected to initial banburying at a certain temperature for a certain period of time, and then a certain amount of solvent is added (or no solvent is added) and the banburying is continued for a certain period of time to prepare a millimeter-level homogenized granule. The temperature range of the initial banburying is 15 to 90°C, and the banburying time of the initial banburying is 10 to 40 minutes. After the initial banburying, the added solvent has a certain viscosity, the viscosity range of the solvent is 1-5000cP, and the mass percentage of the added solvent is 0 to 20%. The banburying time of continued banburying is 20 to 60 minutes.
[0034] like Figures 9 to 11 As shown, in the homogenization step, the homogenizer 100 used is a device equipped with a differential speed dual stirring spiral structure (a first stirring spiral structure 10 and a second stirring spiral structure 20). Fig. 9 As shown, in the first embodiment, the differential double stirring spiral structure can adopt a differential double stirring Σ-shaped blade structure, and a plurality of Σ-shaped blades 2 are arranged side by side on the stirring shafts 1 of the first stirring spiral structure 10 and the second stirring spiral structure 20, respectively. The spiral directions of the blades 2 of the first stirring spiral structure 10 and the blades 2 of the second stirring spiral structure 20 are opposite, and a notch 21 is provided on the Σ-shaped blade 2. Fig.10As shown, in the second embodiment, the differential twin-screw stirring structure can adopt a differential twin-screw structure, and spiral blades 2 are arranged on the stirring shafts 1 of the first stirring spiral structure 10 and the second stirring spiral structure 20, and the spiral directions of the blades 2 of the first stirring spiral structure 10 and the blades 2 of the second stirring spiral structure 20 are opposite. Fig.11 As shown, in the third embodiment, the differential double stirring helical structure can adopt a vertical differential double-axis stirring paddle structure, and spiral blades 2 are arranged on the stirring shafts 1 of the vertical stirring helical structure No. 1 10 and the stirring helical structure No. 2 20, and the spiral directions of the blades 2 of the stirring helical structure No. 1 10 and the blades 2 of the stirring helical structure No. 2 20 are opposite. The rotation speed of the stirring helical structure No. 1 10 is 40-80r / min, and the rotation speed of the stirring helical structure No. 2 20 is 10-70r / min. The homogenizer 100 uses a differential double-stirring spiral structure to knead and homogenize the fibrous material into agglomerates and granulate it in a kneading manner. The granulation process includes kneading and breaking up actions: under the shear force of the differential double-stirring spiral structure, powders of different particle sizes are first kneaded into larger agglomerates, and then the agglomerates are evenly broken up to reach a balanced state after the particle size requirements are met; the granules produced in this way have basically the same particle size and a more uniform particle size distribution, which ensures the uniform distribution of PTFE fibers and light and heavy materials during the film forming process, and significantly improves the uniformity and toughness of the film. Figure 5 The figure shows the state of the electrode powder after homogenization. It can be seen from the figure that after the powder is homogenized, the particles of the granules are clearly separated and have uniform particle sizes. The particle size of the homogenized granules is 1 to 5 mm.
[0035] Step S4: In this step, the homogeneous granules are fed into a calender, and the calender rollers of the calender roll the homogeneous granules into an initial film. The calender can be an existing mature calendering equipment, as long as it can achieve calendering of the homogeneous granules. Figure 6 As shown, the initial membrane obtained by calendering the homogeneous granular material has a smooth membrane surface, and the PTFE fibers and light and heavy materials are evenly distributed during the membrane forming process.
[0036] Step S5: In this step, the initial film is fed into a thinning device, and the initial film is further thinned by a thinning calender roller to obtain a finished film. The thinning device can be an existing mature thinning device as long as it can achieve the thinning operation of the initial film.
[0037] Step S6: In this step, the finished film and the pre-processed current collector are sent to a composite device to composite to obtain an electrode sheet. The composite device can be an existing mature composite device as long as it can realize the composite operation of the finished film and the current collector.
[0038] The prepared electrode membrane can be used to make secondary batteries.
[0039] Electrode granule production example 1: The mixed material uses graphite and carbon nanotubes as trace additives. During mixing, the active material, conductive agent, graphite and carbon nanotubes are first mixed evenly, and then PTFE is added and mixed evenly. The mixed material is fiberized by a disc-type air flow mill. The pressure of the compressed air passed into the disc-type air flow mill is 0.95MPa, the temperature is 70°C, and the humidity is 4%. After the material is fiberized, it is homogenized by a homogenizer 100. The homogenizer 100 adopts a differential double-stirring Σ-type paddle structure. The rotation speed of the No. 1 stirring spiral structure 10 is 56r / min, and the rotation speed of the No. 2 stirring spiral structure 20 is 46r / min. The temperature range of the initial mixing is 50°C, and the mixing time of the initial mixing is 10min. After the initial mixing is completed, no solvent is added, and the mixing time for continued mixing is 50min. The state of the homogenous granular material obtained after homogenization is as follows Figure 7 As shown in the figure, it can be seen that the granules are distinct, there is no adhesion, and there are no small lumps. The average particle size of the homogeneous granules is 2mm and the maximum particle size is 5mm.
[0040] Electrode granule production example 2: The mixed material uses silicate minerals and graphite as trace additives. When mixing, the conductive agent and PTFE are first mixed evenly, and then the active material, silicate minerals, and graphite are added and mixed evenly. The mixed material is fiberized by a fluidized bed jet mill, and the pressure of the compressed air passed into the fluidized bed jet mill is 0.56MPa, the temperature is 80°C, and the humidity is 3%. After the material is fiberized, it is homogenized by a homogenizer 100. The homogenizer 100 adopts a differential double-stirring Σ-type blade structure. The speed of the first stirring spiral structure 10 is 60r / min, and the speed of the second stirring spiral structure 20 is 56r / min. The temperature range of the initial mixing is 15°C, and the mixing time of the initial mixing is 15min. After the initial mixing is completed, 2% of the solvent is added. The solvent is a mixture of polytetrafluoroethylene suspension and polyvinylidene fluoride suspension. The ratio of polytetrafluoroethylene suspension: polyvinylidene fluoride suspension = 1:1, and the mixing time of continued mixing is 20min. The average particle size of the homogeneous granules is 2 mm and the maximum particle size is 5 mm.
[0041] Electrode granule production example 3: The mixed material uses carbonates and carbon nanotubes as trace additives. During mixing, the active material, carbonates and carbon nanotubes are first mixed evenly, and then PTFE is added and mixed evenly. The mixed material is fiberized by a circulating tubular airflow mill. The pressure of the compressed air passed into the circulating tubular airflow mill is 0.82MPa, the temperature is 50°C, and the humidity is 1%. After the material is fiberized, it is homogenized by a homogenizer 100. The homogenizer 100 adopts a differential double-stirring Σ-type paddle structure. The rotation speed of the No. 1 stirring spiral structure 10 is 45r / min, and the rotation speed of the No. 2 stirring spiral structure 20 is 20r / min. The temperature range of the initial mixing is 30°C, and the mixing time of the initial mixing is 25min. After the initial mixing is completed, 14% of the solvent is added, and the solvent is a polyvinylidene fluoride suspension. The mixing time is continued for 60min. The state of the homogenous granules obtained after homogenization is as follows Figure 8 As shown in the figure, it can be seen that the granules are distinct, there is no adhesion, and there are no small lumps. The average particle size of the homogeneous granules is 2mm and the maximum particle size is 5mm.
[0042] Electrode granule production example 4: The mixed material uses phosphate, silicate minerals, and graphite as trace additives. When mixing, the active material, phosphate, silicate minerals, graphite, and carbon nanotubes are first mixed evenly, and then PTFE is added and mixed evenly. The mixed material is fiberized by a target airflow mill, and the pressure of the compressed air passed into the target airflow mill is 0.75MPa, the temperature is 60°C, and the humidity is 2%. After the material is fiberized, it is homogenized by a homogenizer 100. The homogenizer 100 adopts a differential double-stirring Σ-type blade structure, the speed of the first stirring spiral structure 10 is 80r / min, the speed of the second stirring spiral structure 20 is 70r / min, the temperature range of the initial mixing is 70°C, and the mixing time of the initial mixing is 30min. After the initial mixing is completed, 20% of the solvent is added, and the solvent is a sodium carboxymethyl cellulose suspension. The mixing time of continued mixing is 30min. The average particle size of the homogenized granules is 2mm, and the maximum particle size is 5mm.
[0043] Electrode granule production example 5: The mixed material uses graphite, carbon nanotubes, and silicate minerals as trace additives. When mixing, PTFE, graphite, carbon nanotubes, and silicate minerals are first mixed evenly, and then the active material is added and mixed evenly. The mixed material is fiberized by a jet-type air mill, and the pressure of the compressed air passed into the jet-type air mill is 0.63MPa, the temperature is 100°C, and the humidity is 5%. After the material is fiberized, it is homogenized by a homogenizer 100. The homogenizer 100 adopts a differential double-stirring Σ-type blade structure, the speed of the first stirring spiral structure 10 is 75r / min, the speed of the second stirring spiral structure 20 is 10r / min, the temperature range of the initial mixing is 90°C, the mixing time of the initial mixing is 40min, and after the initial mixing is completed, 6% of the solvent is added, the solvent is alcohol, and the mixing time of the continued mixing is 40min. The average particle size of the homogenized granules is 2mm, and the maximum particle size is 5mm.
[0044] Electrode granule preparation example 6: The mixed material uses graphite and silicate minerals as trace additives. When mixing, PTFE, graphite, carbon nanotubes, and silicate minerals are first mixed evenly, and then the active material is added and mixed evenly. The mixed material is fiberized by a target airflow mill, and the pressure of the compressed air passed into the target airflow mill is 0.75MPa, the temperature is 60°C, and the humidity is 2%. After the material is fiberized, a homogenizer 100 is used for homogenization. The homogenizer 100 adopts a differential twin-screw structure, the speed of the first stirring spiral structure 10 is 45r / min, the speed of the second stirring spiral structure 20 is 10r / min, the temperature range of the initial mixing is 70°C, the temperature range of the initial mixing is 70°C, the mixing time of the initial mixing is 30min, and after the initial mixing is completed, 20% of the solvent is added, the solvent is a polytetrafluoroethylene suspension, and the mixing time of the continued mixing is 30min. The average particle size of the homogenized granules is 2mm, and the maximum particle size is 5mm.
[0045] Electrode granule production example seven: The mixed material uses carbon nanotubes and silicate minerals as trace additives. When mixing, PTFE, carbon nanotubes, and silicate minerals are first mixed evenly, and then the active material is added and mixed evenly. The mixed material is fiberized by a disc-type airflow mill, and the pressure of the compressed air passed into the disc-type airflow mill is 0.95MPa, the temperature is 70°C, and the humidity is 4%. After the material is fiberized, it is homogenized by a homogenizer 100. The homogenizer 100 adopts a vertical differential double-axis stirring paddle structure, the speed of the first stirring spiral structure 10 is 60r / min, the speed of the second stirring spiral structure 20 is 56r / min, the temperature range of the initial mixing is 40°C, and the mixing time of the initial mixing is 35min. After the initial mixing is completed, 2% of the solvent is added, the solvent is alcohol, and the mixing time of the continued mixing is 20min. The average particle size of the homogenized granules is 2mm, and the maximum particle size is 5mm.
[0046] The above description is an explanation of the present invention, not a limitation of the present invention. The present invention may be modified in any form without violating the spirit of the present invention.
Claims
1. A dry process for producing electrode granules, characterized in that: The steps include: The active material, the conductive agent, the trace additive and the binder are mixed to obtain a mixed material; Performing fiberization treatment on the mixed material to obtain a fiberized material; A homogenizer (100) is used to homogenize the fiberized material. After the fiberized material undergoes initial internal kneading and continued internal kneading in the homogenizer (100), millimeter-scale homogenous granular material is prepared.
2. The dry electrode granular production method according to claim 1, characterized in that: The homogenizer (100) is provided with a differential double stirring spiral structure. The differential double stirring spiral structure can adopt a differential double stirring Σ-type blade structure, or a differential double screw structure, or a vertical differential double-shaft stirring blade structure. The blade (2) of the first stirring spiral structure (10) and the blade (2) of the second stirring spiral structure (20) have opposite spiral directions.
3. The dry electrode granular production method according to claim 2, characterized in that: The rotation speed of the first stirring spiral structure (10) of the homogenizer (100) is 40 to 80 r / min, and the rotation speed of the second stirring spiral structure (20) is 10 to 70 r / min.
4. The method for producing dry electrode granules according to claim 1, characterized in that: After the initial kneading of the fiberized material, a solvent is added and the kneading is continued. The added solvent is viscous.
5. The method for producing dry electrode granules according to claim 4, characterized in that: The mass percentage of the added solvent is 0-20%; the solvent is viscous, and the viscosity range is 1-5000cP; the solvent is a mixture of polytetrafluoroethylene suspension and polyvinylidene fluoride suspension, or polyvinylidene fluoride suspension, or sodium carboxymethyl cellulose suspension, or alcohol.
6. The method for producing dry electrode granules according to claim 1, characterized in that: During homogenization, the initial mixing temperature range is 15-90°C, the mixing time of the initial mixing is 10-40 minutes, and the mixing time of the continued mixing is 20-60 minutes; the particle size of the homogenized granules is 1-5 mm.
7. The method for producing dry electrode granules according to claim 1, characterized in that: When mixing materials, active substances, conductive agents, trace additives and binders are uniformly mixed in batches, two or more of the materials are first mixed and dispersed or coated, and then the remaining materials are added for mixing and dispersion; the trace additives are one or more of graphite, carbon nanotubes, carbonates, phosphates, and silicate minerals; the binder is one or more of polytetrafluoroethylene suspension, polyvinylidene fluoride suspension, polyvinylidene fluoride suspension, styrene-butadiene rubber emulsion, sodium carboxymethyl cellulose suspension, and alcohols.
8. The method for producing dry electrode granules according to claim 1, characterized in that: The mixed material is fiberized by an air jet mill. The pressure of the compressed air introduced into the air jet mill is 0.5-1MPa, the temperature is 50-100°C, and the humidity is 1%-5%. The air jet mill type is one of the disc air jet mill, circulating tube air jet mill, target air jet mill, jet air jet mill or fluidized bed air jet mill.
9. A dry electrode production method, characterized in that: The homogeneous granules prepared according to the dry electrode granule preparation method of claim 1 are subjected to calendering and thinning treatment to obtain a finished film, and the finished film is compounded with a current collector to obtain an electrode plate.
10. A secondary battery, characterized in that: The electrode sheet is manufactured by using the dry electrode sheet manufacturing method according to claim 9.